Experimental Investigation on a Slurry Pump at Different Operating Parameters - S. A. EL-Agouz; Hagar Mohamed; Elsaid Nossir (Journal of Engineering Research - Egypt, 2020)
Study on slurry pump performance has attracted much interest in many engineering fields. When pumps are required to handle slurries. The pump head and efficiency are mainly affected by the solid size, solid concentration and solid density. Centrifugal slurry pumps are benign used extensively for pipeline transportation systems and phosphate extraction industry because of their capabilities to economically convey large size abrasive solids in bulk. There is a lack of information about the effect of slurry on the performance characteristics of conventional centrifugal pumps when working without and with cavitation. A test rig with a testing centrifugal pump was constructed. The suction pipe between the mixing tank and pump inlet was designed to avoid solid deposition in suction pipe and to keep the pressure loss between the sump and the pump as low as possible. The rig was designed so that the flow rates, suction pressure, rotational speed, and solid concentration could be varied independently. The results showed that the head generating capability and pump efficiency decrease, also the power consumption increases with increasing solid concentration, consequently the head and efficiency of the pump with NPSH decreases with increasing the solids concentration and particle size, and cavitation inception accelerates with increase the solid concentration.